THE NATURAL KITCHEN AS PLACE TO RE-ENCHANTMENT OF THE FEMALE BODY - Fabio Lucio Antunes Guedes; Maristela Oliveira de Andrade (Universidade do Estado do Rio de Janeiro, 2016)
The present study aims to problematize the emergence of natural cuisine in contemporary times based on an ethnography dedicated to the corporeity of holistic therapeutic practice, and its requirement for a specific natural diet. It is presented a small clipping which aims to account for a modern socially structured culinary context in the figure of the chef who is the central character in the historical process of naturalization of animal protein in the human palate and in the de-substantialization of the female soul. The redefinition proposed by natural kitchen plays an important role in the understanding of complex human body sensitivity to the modern carnivorism, experimented throughout the alternative practices (healing and alimentation) performed at the therapeutic center. The non-governmental institution "AFYA - women therapeutic center" located in João Pessoa, Paraíba, Brasil, symbolizes the effort for recognition of the emancipation of the female body, evidencing cooking site as a special locality for re-enchantment of the female body, based on the legitimacy of vegetarianism as empowering device to resignification of feminine soul. DOI: 10.12957/demetra.2016.16025